Expression of heat shock protein Hsp 27 in ovarian carcinoma (2020)
Objective: The aim of the present study was to determine the expression of heat shock protein 27 (Hsp 27) in patients with ovarian carcinoma and its relationship with clinical and histopathological characteristics. Materials and Methods: Cross-sectional study in patients diagnosed with ovarian carcinoma. From paraffin blocks with tumor material, archived in the pathology services of the San Jose and Infantil Unversitario de San Jose hospitals since 2013 to 2016 the expression of Hsp 27 was analyzed using a semi-quantitative measurement method. Patients´ clinical records were reviewed to analyze clinical and histopathological characteristics. Results: Immunohistochemistry was performed on 31 patients. Hsp 27 immunostaining was positive in more than 50% of tumor cells in 17 (54.8%) cases. The intensity of Hsp 27 expression was strong in 13 (41.9%) cases. The most frequent location was membranous and cytoplasmatic in 25 (80.6%). The characterization of patients with intensity of 3+ occurred mainly in high-grade serous papillary stage IIIC carcinomas. Conclusion: A stronger Hsp 27 expression occurred mainly in patients with high-grade serous, histology, advanced FIGO stage and in whom optimal or complete cytoreduction could not be performed.